2016
DOI: 10.1177/0004867416682599
|View full text |Cite
|
Sign up to set email alerts
|

A three-decade repeated cross-sectional survey on mental health of the Chinese Jino minority

Abstract: Results from our three-decade longitudinal repeated cross-sectional survey show that due to rapid social, economic and cultural changes among the Jino people, serious social and mental health problems such as alcohol-related disorder, suicide and major depressive disorders have increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…[ 19 ] It is also higher than the rates found by surveys in some Western countries, ranging from 1.3% to 7.4%. [ 20 – 22 ] The prevalence of MDD and mood disorder is higher in Dulong people than that found in other surveys in Yunnan Province (2.4% among the Jino nationality and 1.96% in Kunming) [ 4 , 18 , 23 ] and in China. However, the prevalence of MDD and mood disorder is lower than that in the United States.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…[ 19 ] It is also higher than the rates found by surveys in some Western countries, ranging from 1.3% to 7.4%. [ 20 – 22 ] The prevalence of MDD and mood disorder is higher in Dulong people than that found in other surveys in Yunnan Province (2.4% among the Jino nationality and 1.96% in Kunming) [ 4 , 18 , 23 ] and in China. However, the prevalence of MDD and mood disorder is lower than that in the United States.…”
Section: Discussionmentioning
confidence: 92%
“…[ 3 ] The evolution of society and economic changes in Chinese society have had a profound influence on the 56 ethnic groups in China. [ 4 , 5 ] Studies have shown that in many countries around the world, minority groups face a higher likelihood of mental disorders. [ 3 ] In this context, the mental status of Chinese ethnic minorities deserves attention, but there is little research on this topic.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations